Okul müdürlerinin vizyoner liderlik özelliklerinin okul etkililiği ile arasındaki ilişkinin incelenmesi - Uçak, Zeynep (İstanbul Sabahattin Zaim Üniversitesi, 2023)
Bu araştırmanın amacı "Öğretmenlerce Algılanan Okul Müdürlerinin Vizyoner Liderlik Özelliklerinin Okul Etkililiği İle Arasındaki İlişkinin İncelenmesi" olarak belirlenmiş ve araştırmanın gerçekleştirilmesinde nicel araştırma yöntemlerinden ilişkisel tarama modeli kullanılmıştır. Araştırma evrenini İstanbul sınırları içerisinde 2021-2022 Eğitim Öğretim döneminde görev yapan; kolayda örnekleme yöntemiyle oluşturulan özel ve devlet okullarında görevli 396 öğretmen oluşturmuştur. Araştırmada veri toplama aracı olarak "Kişisel Bilgi Formu", "Vizyoner Liderlik Ölçeği" ve "Okul Etkililik Ölçeği" kullanılmıştır. Elde edilen verilere uygulanan t-Testi analizi neticesinde; okul müdürlerinin vizyoner liderlik özellikleri ve okul etkililiği "yüksek düzeyde" tespit edilmiştir. ANOVA analizi neticesinde değişkenler, demografik özelliklere göre anlamlı farklılıklar göstermiştir. Okul müdürlerinin vizyoner liderlik özellikleri ve okul etkililiği arasında pearson korelasyon analizi bağlamında tüm alt boyutlarda anlamlı ve pozitif yönde "orta düzeyde" ilişki olduğu görülmüştür. Yapılan çoklu regresyon analizi neticesinde vizyoner liderliğin okul etkililiğini "orta düzeyde" ve pozitif yönde anlamlı şekilde yordadığı saptanmıştır.

The aim of this research was determined as "Examination of the Relationship Between the Visionary Leadership Characteristics of School Principals Perceived by Teachers and School Effectiveness" and the relational survey model, one of the quantitative research methods, was used in the realization of the research. The population of the research is those who work within the borders of Istanbul in the 2021-2022 academic year; The sample consisted of 396 teachers working in private and public schools, which were formed by convenience sampling method. "Personal Information Form", "Visionary Leadership Scale" and "School Effectiveness Scale" were used as data collection tools in the research. As a result of the normality test and t-Test analysis applied to the obtained data; School principals' visionary leadership characteristics and school effectiveness were determined at a "high level". As a result of the ANOVA analysis, the variables showed significant differences according to the demographic characteristics. In the context of Pearson correlation analysis between school principals' visionary leadership characteristics and school effectiveness, it was observed that there was a significant and positive "moderate" relationship in all sub-dimensions. As a result of the multiple regression analysis, it was determined that visionary leadership significantly predicted school effectiveness in a "moderate" and positive direction.
Examination of the relationship between school principals' visionary leadership characteristics and school efficiency
Keywords: Liderlik; Vizyoner Liderlik; Okul Etkililiği; Leadership; Visioner Leadership; School Efficiency